MNEs and financing climate change transitions: the challenge of collective action - Zahra, Shaker A. (Journal of International Business Studies, 2025)
Allen et al. (2024a) present an insightful and comprehensive analysis of the role multinationals (MNEs) can play in tackling worldwide climate change challenges. Acknowledging that this role is complex and multifaceted, they pay special attention to the financing of climate change initiatives and the unique advantages MNEs have in this regard. I reflect on Allen et al.’s key arguments and proposals and their underlying assumptions, which I found to be overly optimistic on multiple grounds. The common denominator in the range of issues and questions I raise is the challenge of coordinating collective action – either among nation-states, MNEs, NGOs, or some combination thereof – on what is inherently a global-scale issue. I conclude by outlining a future research agenda.